Feasibility of clinical and electrocardiographic follow-up of prinzmetal angina using the metaverse. Issue 4 (22nd December 2022) - Skalidis, I; Maurizi, N; Kaldasch, M; El Idrissi, B; Briante, N; Fournier, S; Muller, O; Skalidis, E
Abstract: Background: The recent pandemic triggered an acceleration in adopting innovative technologies and telemedicine novelties. The metaverse, representing a merge of digital worlds using augmented reality (AR) and virtual reality (VR), promises disruptive transformation in healthcare. The feasibility of combining the metaverse with cardiovascular telemedicine services empowering remote consultation as well as assisting heart disease prevention and diagnosis, has not been investigated yet in cardiology. Purpose: We evaluated the feasibility of combined clinical and electrocardiographic follow-up inside the metaverse on top of standard of care for a patient who presented with prinzmetal angina. Methods: A digital consultation room combining AR/VR was created in a metaverse platform (GDPR compliant, CE marked class I medical device). Patient and cardiologist were given a personal and secured login account. Interactions and connections were made via virtual avatars. Patient was instructed to ask for a consultation in case of any cardiac related symptom occurred. The patient was equipped with a previously validated portable hospital-grade 12-lead smartphone-based electrocardiograph device which was directly integrated to the metaverse platform. Results: A 30 years old obese active smoker patient presented for recurrent episodes of typical cardiac chest pain at rest. ECG showed sinus rhythm, normal atrioventricular and intraventricular conduction and no repolarization abnormalities. Laboratory test were normal, echocardiography showed a normal biventricular function with no focal abnormalities or valvular disease. Coronary angiogram excluded the presence of coronary artery disease, and the most possible diagnostic scenario was prinzmetal angina from coronary artery spasm. The patient was therefore discharged under treatment with diltiazem 120 mg twice daily, a multiple lead smartphone ECG device as well as the access to metaverse via his avatar, since no ECG were available during the episodes. Ten days later, the patient experienced an episode of palpitation accompanied with general discomfort. He subsequently logged into the metaverse where the cardiologist was available. The anamnesis of the episode was collected as well as the auto-recorded ECG by the patient. Although the clinical and electrocardiographic data were reassuring, the physician proposed to seek for medical attention. Hospital work up was consistent with the diagnosis provided in the virtual consultation. Conclusions: To our knowledge, we conducted the first medical act in cardiology inside the metaverse combining VR environment with existing cardiovascular technological innovations as support information to the standard of care. Exploiting the full potential of the metaverse could serve as an unparalleled leap in the way cardiovascular medicine is delivered and could introduce new dimensions to cardiology in terms of health education, disease prevention and diagnosis. Funding Acknowledgement: Type of funding sources: None.